2022
DOI: 10.3390/v14010127
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Viability of Senecavirus A in Exposed House Flies (Musca domestica)

Abstract: House flies (Musca domestica) are often present in swine farms worldwide. These flies utilize animal secretions and waste as a food source. House flies may harbor and transport microbes and pathogens acting as mechanical vectors for diseases. Senecavirus A (SVA) infection in pigs occurs via oronasal route, and animals shed high virus titers to the environment. Additionally, SVA possesses increased environmental resistance. Due to these reasons, we investigated the tenacity of SVA in house flies. Five groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The linear regression model with 95% confidence interval indicated an expected viability between 403 and 624 days in the spleen, 565 to 1274 days in the BM-calf, and between 336 and 578 days in the BM-pig. These results corroborate findings from previous studies that demonstrated increased viability of SVA in various conditions and temperatures [ 13 , 17 , 18 ]. The SVA results also align with studies reporting FMDV viability in the bone marrow for up to 7 months when stored at 1–4 °C [ 19 ] and 77 days in muscle when stored at 4 °C [ 20 ].…”
Section: Resultssupporting
confidence: 92%
“…The linear regression model with 95% confidence interval indicated an expected viability between 403 and 624 days in the spleen, 565 to 1274 days in the BM-calf, and between 336 and 578 days in the BM-pig. These results corroborate findings from previous studies that demonstrated increased viability of SVA in various conditions and temperatures [ 13 , 17 , 18 ]. The SVA results also align with studies reporting FMDV viability in the bone marrow for up to 7 months when stored at 1–4 °C [ 19 ] and 77 days in muscle when stored at 4 °C [ 20 ].…”
Section: Resultssupporting
confidence: 92%
“…In contrast, other swine pathogens especially those involved with respiratory disease such as porcine respiratory and reproductive syndrome virus are diagnosed in a higher percentage during colder months in the fall and winter (38). Previous work has reported that house flies (Musca domestica) tested positive for SVA nucleic acids (17,39); therefore, they could serve as a mechanical vector to spread SVA, which has been shown for other viruses and bacteria (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is necessary to evaluate the transmission routes within pig populations and through mechanical vectors like flies. 24 In addition, retrospective serological studies from symptomatic and asymptomatic pigs will help determine the timing of SVA introduction in Mexico. These results will increase the knowledge regarding SVA epidemiology and highlight the significant SVA surveillance role in Mexican swine populations to prevent SVA reintroduction and further spread.…”
Section: Contemporary Strainsmentioning
confidence: 99%